Pengamatan Hama Terpadu Tanaman Padi - Tri Yaninta Ginting; Luthfia Zahra; Durio Jibetius Sebayang; Jon Alex Sihombing; Inbha Raz; Iqbal Kurniawan Tarigan; Imam Firmansyah; Edi Suranta Sinaga (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the population dynamics of rice plant pests through periodic monitoring during 8 weeks of observation. The research was conducted on 5 rice field plots using direct sampling method and yellow trap. The observation data included 23 pest species from various families such as Acrididae, Muscidae, Culicidae, Lycosidae, Pieridae, Chrysomelidae, and others. Observations showed that pest populations fluctuated during the observation period, with some species showing a downward trend such as mosquitoes (Culicidae) from an average of 19.6 individuals/map in the first observation to 14.2 individuals/map in the last observation, while some other pests such as snail carp (Pomacea canaliculata) showed significant variation. Pests that were consistently found in high numbers were mosquitoes, mealybugs (Pieris rapae), and gold snails. This periodic monitoring provides important information for integrated pest control strategies in sustainable rice cultivation.